Pengembangan Bisnis Pembuatan Website Company Profile dan Portofolio pada Nest Link - Muhammad Farhan Fahrezy; Adli Farizi; Cahya Rudiansah; Wien Kuntari (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The development of digital technology has transformed how companies present themselves online, with company profile and portfolio websites becoming crucial tools in building image and credibility in the digital market. This research aims to identify business opportunities in the website development industry, particularly for small and medium enterprises (SMEs), using NestLink as a case study. Utilizing the Business Model Canvas (BMC) method, the research analyzes the business model components of NestLink in providing website development services.The research results show that NestLink offers customized website solutions, including company profile website creation, ready-to-use templates, and portfolio websites. Distribution channels include social media, official websites, and digital advertising. The main strategy focuses on responsive design, good user experience, and flexible templates. The primary revenue comes from website development services and template sales.